Consumers' experiences of rights-based mental health laws: Lessons from Victoria, Australia. (September 2021) - Maylea, Chris; Katterl, Simon; Johnson, Brendan; Alvarez-Vasquez, Susan; Hill, Nicholas; Weller, Penelope
Abstract: Many countries embarked on reforms of mental health law in the wake of the Convention on the Rights of Persons with Disabilities. These reforms have had varying levels of success. This paper considers the experience of consumers in the Victorian mental health system, drawing on an evaluation that asked consumers and clinicians about their knowledge and experience of rights under the Victorian Mental Health Act, 2014. The data show that consumers were not informed of their rights, were not involved in decisions about treatment, were not able to access safeguards, and could not exercise their rights. The explanations for this include limited staff time, unclear delegations of responsibility, a lack of knowledge, training, and support for rights, and a preference for 'best interests' approaches. The paper identifies tangible reforms that would maintain rights for consumers, including competent refusal of treatment, legislative and regulatory reforms, and training and resourcing. Consumers in this study found that the rights-based framework in the Mental Health Act, 2014 had such an insignificant effect on clinical mental health practice in Victoria that their rights appeared to be illusory.